Emergency Medicine Ultrasound Simulation (US/S) Case Scenario Package - Leo Kobayashi; Marc Shapiro; Arun Nagdev; Frantz Gibbs (MedEdPORTAL, 2010)
Abstract This resource consists of a modular package containing five high-fidelity full-body simulation case scenarios with supplemental bedside emergency department ultrasound videos (deidentified) to assist in emergency medicine decision-making training. Developed for our emergency medicine residency curriculum, this ultrasound simulation program supplements established educational interventions in which residents learn basic emergency ultrasound principles and are mentored individually in standard image-acquisition techniques on consenting patients. Emergency ultrasound and medical simulation faculty collaborated on a program to help trainees apply bedside sonography in real time to critical patient care decisions inside a risk-free learning environment. To generate simulated images necessary for emergency ultrasound application training, we compiled a PC-based sonographic image library of deidentified normal and pathologic findings. To minimize cost, a donated laptop was loaded with imaging software and the sonographic library, attached to a nonfunctioning ultrasound probe, and placed on an IKEA cart approximating commercially available emergency ultrasound stands. The five cases feature high-acuity simulation scenarios with occult but profound pathology requiring rapid decision making based on appropriate emergency ultrasound utilization: (1) right ventricular strain accompanying pulseless electrical activity from massive pulmonary embolism, (2) pericardial tamponade in a hypotensive uremic patient, (3) serial FAST (focused abdominal sonography in trauma) exams with interim development of detectable hemoperitoneum in a trauma patient, (4) Morrison's pouch fluid in a hypotensive female with ruptured ectopic pregnancy, and (5) leaking abdominal aortic aneurysm in an elderly patient with back pain. The inclusion of sonographic movie files in the clinical scenarios adds significantly to simulation verisimilitude for participants. This course has been incorporated in the Warren Alpert Medical School's emergency medicine residency education program at Brown University.